Importance of studying the term “information space” in modern philosophy - Zhuldyz Imanbayeva, Asset Kuranbek, Doszhan Balabekuly, Jakipbek Altayev, Abdullah Kizilcik, (Opción, 2020)
The paper aims to investigate the importance of studying the term “information space” in modern philosophy via a socio-philosophical analysis as a method. As a result, information culture is a combination of informative and communicative tools made during the whole cultural and historical development that takes part in the socialization of an individual and a social mind. In conclusion, the purpose of using a systematic analysis in a particular problem is to analyze a lot of information about the system using the methodology and to increase the validity of a large number of possible solutions